2022
DOI: 10.3390/nano12122017
|View full text |Cite
|
Sign up to set email alerts
|

γ-Valerolactone Production from Levulinic Acid Hydrogenation Using Ni Supported Nanoparticles: Influence of Tungsten Loading and pH of Synthesis

Abstract: γ-Valerolactone (GVL) has been considered an alternative as biofuel in the production of carbon-based chemicals; however, the use of noble metals and corrosive solvents has been a problem. In this work, Ni supported nanocatalysts were prepared to produce γ-Valerolactone from levulinic acid using methanol as solvent at a temperature of 170 °C utilizing 4 MPa of H2. Supports were modified at pH 3 using acetic acid (CH3COOH) and pH 9 using ammonium hydroxide (NH4OH) with different tungsten (W) loadings (1%, 3%, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 135 publications
0
2
0
Order By: Relevance
“…The 60NiAl wi precursor sample was easily reduced, appearing as two reduction peaks with maxima at 275 and 290 °C and a wide shoulder zeroing at about 700 °C. This profile indicates that the main fraction of NiO interacts weakly with γ-Al 2 O 3 , while a smaller part interacts moderately with it [ 36 , 37 ]. However, the XRD results ( Figure 3 ) showed that the corresponding catalyst activated at 400 °C contained a significant amount of NiO, and one should expect that this NiO would be reduced at higher temperatures, but according to H 2 -TPR results ( Figure 4 ), this was not the case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 60NiAl wi precursor sample was easily reduced, appearing as two reduction peaks with maxima at 275 and 290 °C and a wide shoulder zeroing at about 700 °C. This profile indicates that the main fraction of NiO interacts weakly with γ-Al 2 O 3 , while a smaller part interacts moderately with it [ 36 , 37 ]. However, the XRD results ( Figure 3 ) showed that the corresponding catalyst activated at 400 °C contained a significant amount of NiO, and one should expect that this NiO would be reduced at higher temperatures, but according to H 2 -TPR results ( Figure 4 ), this was not the case.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction peak at 330 °C is attributed to NiO weakly interacting with Al 2 O 3 . The wide reduction peak extended from 410 up to 880 °C shows, in addition, the formation of various NiO-species, which interact stronger with Al 2 O 3 forming non-stoichiometric surface aluminates (NiAlxOy) that are highly dispersed on the surface of the support, and stoichiometric NiAl 2 O 4 [ 37 ]. Finally, we have to note that the hydrogen consumption in the 60NiAl cp sample was found to be 42% higher than that in the 60NiAl wi .…”
Section: Resultsmentioning
confidence: 99%